'Got a degree...all of a sudden I'm in a Jobcentre': The role of 'stigma' in 'precarious' graduate transitions. (11th October 2017) - Formby, Adam Paul
Abstract : There is widespread evidence that those claiming out-of-work benefits experience different types of 'benefit stigma' in the UK, with the focus largely falling on conventionally disadvantaged welfare users. In contrast, graduates' experiences of 'benefits stigma' go unnoticed because of their relative advantage within the labour market. Yet, an increase in precarity across the labour market has unsettled graduate transitions and is re-shaping their relationships with out-of-work benefits. Against this backdrop, this article explores how graduates respond to different aspects of 'benefit stigma'. It posits that challenging stigmatising narratives associated with out-of-benefits – is integral to support graduates furthest away from knowledge-based economy jobs.